Research on Intrinsic Motivation Strategies and Chinese Learning Outcomes of Second Language Learners Based on Self-Determination Theory - Feng, Chenyang (Pinnacle Academic Press Proceedings Series, 2026)
This study focuses on the application of self-determination theory (SDT) in stimulating intrinsic motivation among second language learners and enhancing their Chinese learning outcomes. As global interest in the Chinese language continues to grow rapidly, educators face persistent difficulties in maintaining long-term student interest and active participation. Through comprehensive theoretical analysis and rigorous practical investigation, the research identifies the underlying mechanisms by which learner autonomy, competence, and relatedness needs directly influence language acquisition processes. Furthermore, it proposes actionable pedagogical strategies to promote and sustain intrinsic motivation across diverse educational contexts. Current challenges in Chinese language learning, such as low learner engagement, insufficient autonomous learning capabilities, and significant motivational decay over time, are systematically addressed through targeted motivational strategies. Optimization paths developed in this study include the implementation of autonomy-supportive teaching methodologies, targeted competence enhancement exercises, active social interaction facilitation, and sustainable motivational curriculum design. By integrating these critical elements into daily instructional practices, educators can successfully create a more supportive, inclusive, and highly engaging learning environment. Ultimately, the study provides robust practical guidance for improving overall Chinese learning effectiveness, fostering resilient learner motivation, and significantly advancing contemporary academic research on motivation-driven second language acquisition frameworks.